Language And Culture: Ujung Tradition As One Of The Methods Of Understanding Culture - Haryanto, Sigit (Prosiding University Research Colloquium, 2021)
Understanding culture may through many methods. One of them is custom and tradition. Tradition that is selected to know the culture is ujung tradition. It is Javanese heritage that is still acted in Surakarta and its vicinity. This tradition deals with Eid Al-Fitr. The main activities are visiting to parents, neigbors, and society with happily holiday. One of the main focuses is what the ideas are in it. The data that were colleted by participant observation and depth interview then analysed by using descriptive analytics have results as follows: the ideas in ujung traditions are manners, respect, alms, friendship, and confession of sin. Seeing that many positive ideas in ujung tradition, it is suggested to be preserved and thaught to the children.